Rendering Christian Symbols Fluid: Regarding the Anti-Oppressive Practices of the Feminist Collective L’autre Parole - Couture, Denise (Liberatio)

(untitled) (PUM, 2024)
The purpose of this text is to establish connections between the anti-oppressive practices of the feminist and Christian collective L’autre Parole (“the Other Word”), based in Quebec (Canada), and the orientations of liberation theologies on the global stage. The text highlights how Christian feminists from a local community bend, forge, change and rewrite the symbols of domination within the Christian tradition to restore their liberating thread. In this text, we study, in particular, the symbols of Dieue and of Christa. L’autre Parole’s feminism unfolds as a way of living. It posits the hypothesis of a systemic subordination of women to men as a group and it is encapsulated by two key slogans: “The personal is political” and “A woman will not be liberated until all women are liberated.” The article emphasises how the group can challenge its own complicity with forces of domination or collaboration. While possessing a local and temporary character, the anti-oppressive (re)interpretations of Christian symbols proposed by a local group contribute to a global momentum, hence, the interest in analysing such local creations in order to consider the process of global solidarity in action regarding liberation theologies.